2000
DOI: 10.1037/0021-843x.109.1.150
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness-based cognitive therapy reduces overgeneral autobiographical memory in formerly depressed patients.

Abstract: Previous research on depressed and suicidal patients and those with posttraumatic stress disorder has shown that patients' memory for the past is overgeneral (i.e., patients retrieve generic summaries of past events rather than specific events). This study investigated whether autobiographical memory could be affected by psychological treatment. Recovered depressed patients were randomly allocated to receive either treatment as usual or treatment designed to reduce risk of relapse. Whereas control patients sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
267
4
14

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 417 publications
(301 citation statements)
references
References 25 publications
16
267
4
14
Order By: Relevance
“…[46][47][48] Collaborative care models involving depression care managers have been shown to improve the quality of depression care, symptom severity, patient satisfaction, and functional impairment. 8,40 A few of these trials utilized empirically based psychotherapy as a treatment option for treatment resistant depression. 47,49 Unfortunately, psychotherapy in these trials was delivered as part of a package of collaborative care and its unique contribution to improved outcomes cannot be assessed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[46][47][48] Collaborative care models involving depression care managers have been shown to improve the quality of depression care, symptom severity, patient satisfaction, and functional impairment. 8,40 A few of these trials utilized empirically based psychotherapy as a treatment option for treatment resistant depression. 47,49 Unfortunately, psychotherapy in these trials was delivered as part of a package of collaborative care and its unique contribution to improved outcomes cannot be assessed.…”
Section: Discussionmentioning
confidence: 99%
“…2 Of the estimated 13% that will experience MDD in their lifetimes, 20% will experience chronic depression and 60-85% will experience relapse or recurrence. 2,3 Providers have access to several effective and efficacious treatment options, including a wide array of antidepressant medications [4][5][6][7][8] and psychotherapeutic interventions. [9][10][11][12][13] For chronic MDD, a combination of psychotherapy and medication has been found to be the most effective.…”
mentioning
confidence: 99%
“…The imagined events were categorized as one of three types (Williams et al, 2000): (1) specific events, defined as personal future events that happen in a particular place and time and last for one day or less (e.g., "I imagine it is Christmas Eve, we are at home and my children are giving me a present"); (2) categoric events, referring to a category of events that occur repeatedly over a period of time (e.g., "I am going to take an apartment and I don't have many friends, so I think I will often be alone; I see that as a general situation"); and (3) extended events, which correspond to a series of events that last for longer periods of time (i.e., events occurring over more than a day; e.g., "I imagine next summer, my wife and children will be away on holidays for a week and I will be alone at home"). Following Baddeley and Wilson's (1986) method, responses were scored on a scale from 3 to 1, with higher scores reflecting greater specificity.…”
Section: Experimental Task Assessing Future Projectionmentioning
confidence: 99%
“…Recent studies have shown that short courses of training in state mindfulness can increase a characteristic of autobiographical memories known as specificity (Hargus, Crane, Barnhofer and Williams 2010;Heeren, van Broeck and Philippot 2009;Williams, Teasdale, Segal and Soulsby 2000). Specificity refers to the degree to which individuals retrieve specific memories for personal experiences when asked to do so; that is, memories that occurred at a particular time and place and lasted less than one day.…”
Section: Introductionmentioning
confidence: 99%
“…Their reduced specificity is usually accompanied by overgeneral memory characterised by an increase in the recall of categoric memories, a type of general memories that summarise a category of repeated events (e.g., Williams et al 2007;Williams and Dritschel 1992). Williams et al (2000) showed that mindfulness-based cognitive therapy (MBCT) increased memory specificity and reduced overgeneral memory in formerly depressed patients. The mindfulness techniques taught in this programme of eight weekly classes and daily homework exercises aim to develop awareness of the present moment and sensory processing rather than higher-order processing, and acceptance rather than avoidance of cognitions that arise.…”
Section: Introductionmentioning
confidence: 99%